Application of structural equation modelling in construction management research - Sia, Mal Kong; Gomez, Christy Pathrose; Abd. Hamid, Zuhairi (David Publishing, 2010)
This paper, based on Deming’s quality management (QM) theory embodied in ISO 9001, uses structural equation modelling (SEM) in a construction management research. Based on 100 usable responses collected from a nationwide survey carried out from 14th February to 30th May 2008 on all key players in the Malaysian construction value chain, this paper aims to: (a) validate the dimensions of registration efforts to obtain and maintain ISO 9001 certifications; (b) validate the eight QM principles in ISO 9001 for quality management system (QMS) practices; (c) determine the components of organisational improvements experienced as a result of ISO 9001 certifications in terms of company competitiveness, customer satisfaction, and business performance; and (d) investigate the causal relationships among registration efforts, QMS practices, company competitiveness, customer satisfaction, business performance of ISO 9001–certified companies. The knowledge gained from the application of SEM is an important contribution to the body of theoretical literature in QM.